A range extension for an Australian katydid, Zaprochilus australis (Tettigoniidae; Zaprochilinae) - Rentz, Dcf (Zootaxa, 2015)
The Pollen and Nectar-feeding katydids (Zaprochilinae) are an entire subfamily comprising four genera with species wholly confined to Australia. All are flimsy, soft-bodied and rather clumsy katydids. They are prognathous (Fig. 1A) and have the mouthparts adapted for their unusual habits of feeding on pollen and nectar. All fully winged species in Zaprochilus have peculiarly “rolled” wings (Fig. 1D). In addition, most are active during winter or spring and early summer, Rentz (1993).